The Scales for Assessing Emotional Disturbance–Third Edition: Reliability and Validity of the Screener. (June 2022) - Huscroft-D'Angelo, Jacqueline; Wery, Jessica; Martin-Gutel, Jodie D.; Pierce, Corey; Loftin, Kara
The Scales for Assessing Emotional Disturbance Screener–Third Edition (SAED-3) is a standardized, norm-referenced measure designed to identify school-age students at risk for emotional and behavioral problems. Four studies are reported to address the psychometric status of the SAED-3 Screener. Study 1 examined the internal consistency of the Screener using a sample of 1, 430 students. Study 2 investigated the interrater reliability of the Screener results across 123 pairs of teachers who had worked with the student for at least 2 months. Study 3 assessed the extent to which the results from the Screener are consistent over time by examining test–retest reliability. Study 4 examined convergent validity by comparing the Screener to the Strength and Difficulties Questionnaire (SDQ). Across all studies, samples were drawn from populations of students included in the nationally representative normative sample. The averaged coefficient alpha for the Screener was .88. Interrater reliability coefficient for the composite was .83. Test–retest reliability of the composite was .83. Correlations with the SDQ subscales ranged from .74 to .99, and the correlation of the Screener to the SDQ composite was .99. Limitations and implications for use of the Screener are discussed.